PENENTUAN KANDUNGAN LOGAM Cd DAN Cu DALAM PRODUK IKAN KEMASAN KALENG SECARA SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Tehubijuluw, Hellna; Fransina, Eirene.G.; Pada, Semuel Simra (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry); Volume 1, No. 1, 2013, 2013)
Determination of cadmium and copper concentration of canned fish have been done. Some canned fished were taken away from three mercks circulating in a market and marked as RS (the 1 st sample), NF(2 nd sample), and CP(3 rd sample). The aim of this research is to determine of  cadmium (Cd) and copper (Cu) content of canned fish and to compare the content with the standard limit regulated by the Directorate General of Drug and Food Control No: 03725/B/SK/VII/89. Determination of metal concentration was conducted using  atomic absorption spectrophotometer (AAS). It was found that Cd concentrations of RS and  NF samples are 0.1969 mg/kg and0.0448 mg/kg, respecively while for  CP it was not detected. For Cu concentrations of  RS, NF, and CP are 3.3303 mg/kg, 4.6130 mg/kg, 3.3047 mg/kg  respectively. The results indicated that the samples of the canned fishes  have been contaminated with Cd and Cu metals although the levels of those metals are still lower than  the maximum limit regulated by the Directorate General of Drug and Food Control No: 03725/B/SK/VII/89 where the maximum limit for Cd and  Cu are 0,2 mg.kg and 5.0 mg/kg respectively.
Keywords: Key words:, cadmium, canned fish, copper